Investigação molecular de flavivírus em pacientes febris com suspeita de dengue em Mato Grosso - Heinen, Letícia Borges da Silva (2014)
The genus Flavivirus, Flaviviridae family, comprises arboviruses such as the medical important dengue virus (DENV) and yellow fever virus, involved in febrile illness epidemics in urban and rural areas of tropical and subtropical regions. In Brazil, DENV and Saint Louis encephalitis (SLEV) virus are currently the two most important flaviviruses circulating in urban areas. Since the introduction and emergence of different DENV serotypes in the 1980´s, extensive dengue outbreaks have been reported throughout the country.SLEV, previously recognized only in enzootic cycles without medical relevance in Brazil, has been implicated to febrile illness etiology during dengue fever outbreaks in the Southeast region. The aim of this study was to investigate the circulation of flaviviruses in patients with acute febrile illness suspected of harboring dengue in Mato Grosso (MT) between 2011 and 2012. Material and Methods: 604 serum samples obtained between October 2011 and July 2012 from patients with acute febrile illness suspected of dengue lasting less than 5 days in MT were subjected to multiplex semi-nested RT-PCR for flaviviruses, including all four serotypes of DENV, SLEV Yellow Fever, West Nile, Rocio, Bussuquara, Iguape and Ilheus viruses. Positive samples were tested at least twice in independent single-nested RT-PCR reactions and subjected to nucleotide sequencing of the envelope glycoprotein (E) gene region for phylogenetic analysis. Results: Among 604 patients, 315 (52.2 %) were positive for DENV-4, 24 (4.0 %) for DENV-1, three (0.5 %) for SLEV, one (0.2 %) for DENV-2 and one (0.2 %) for DENV-3. All patients are residents in urban areas of 17 cities of MT. Among then, 9 were co-infections among DENV-1/DENV-4, 1 between DENV-2/DENV-4, two between SLEV/DENV-4 and one with SLEV/DENV-1/DENV-4. The other flaviviruses were not detected. Negative samples for flavivirus totaled 273/604 (45.20 %). Discussion: The occurrence of arboviruses in the population generally is underestimated, probably due to unapparent infection or unspecific clinical presentation, associated to the absence of differential diagnosis. The DENV-4 serotype was introduced in MT in 2012, responsible for the largest number of cases in Cuiabá and Varzea Grande. Co-infections are common when hiperendemic circulation of all four serotypes of DENV is observed. This situation has already been reported in Brazil in Manaus and Rio de Janeiro cities in 2011. Three patients were positive for SLEV in Cuiaba and Várzea Grande. SLEV infections are primarily mild or unapparent. In MT, species of Culex and other vectors are widely dispersed. As humans are final hosts and, therefore, present low titer viremia, the occurrence of SLEV in the population is probably underestimated. Conclusion: DENV-1 and DENV-4 were the most frequently flaviviruses identified. The four DENV serotypes were detected in Cuiaba and sporadic SLEV infections were identified in patients co-infected with DENV-4 or DENV-1/DENV-4 in Cuiaba and Várzea Grande, indicating that other arboviruses may circulate silently during dengue epidemics in urban areas of MT.